Effects of number of simulated particles on the uncertainty in simulation of dispersion of radioactive material using FLEXPART program - Nguyen , Hao Quang; Hoang , Sy Than; Duong , Duc Thang; Pham , Kim Long (Nuclear Science and Technology, 2019)
FLEXPART software simulates atmospheric emissions based on wind-field movements and random disturbances. To simulate random processes, FLEXPART uses a certain number of simulation particles. Changing the number of simulation particles causes a change in the simulated results of the dispersion concentration of the radionuclides. The larger number of simulated particles results in the more accurate simulated results. However, increasing the number of simulated particles results in the increasing of the computational cost. The report presents an assessment of the uncertainty in the concentration of radionuclides in simulating dispersion of 137Cs and 131I nuclides using FLEXPART software according to the number of simulation particles. The number of simulation particles used in this study are 100, 1000, 5000, 7500, 10000, 15000, 20000, 25000 and 30000 particles / hour. Using the image processing software OpenCV to evaluate the uncertainties of simulated results according to the number of simulated particles used. Evaluation results show that the simulated results are acceptable with the number of simulated particles being of 20000 particles/hour.